Analisis Faktor-Faktor yang Memengaruhi Stunting di Indonesia Tahun 2021 - Hardinata, Rizki; Oktaviana, Lisda; Husain, Farah Fadhilah; Putri, Syofmarlianisyah; Kartiasih, Fitri (Seminar Nasional Official Statistics, 2023)
Stunting is a problem that arises from a lack of nutrition and can interfere with the growth and development of children. The high prevalence of stunting can be an indicator of the low quality of a country's human resources. The impacts include limited cognitive abilities, low productivity, and a high risk of disease, which have a long-term negative impact on the preservation of the country. Therefore, stunting is one of the targets of the Sustainable Development Goals (SDGs). The purpose of this study was to analyze the factors that influence the prevalence of stunting in Indonesia in 2021. This study used a cross-sectional approach with secondary data from the Central Bureau of Statistics and the Indonesian Ministry of Health. The research methods used are descriptive analysis and inferential analysis with multiple linear regression. The results showed that the proportion of low-birth-weight babies significantly increased the prevalence of stunting. On the other hand, the proportion of households that had access to sanitation allowed it to significantly reduce the prevalence of stunting in Indonesia.